Pendidikan Kesehatan Dan Simulasi Pelajar Siap Siaga Bencana Gempa Bumi Di SDN Sukajadi Kabupaten Subang - Nuridha Fauziyah; Wardah Fauziah; Minanton; Fitri Handayani; Novian Mahayu Adiutama; Habsyah Saparidah Agustina; Bayu Nirwana; Irfani Nurfuadah; Ade Nuraeni; Rosiah; Dwi Diana Putri (CV. Multi Kreasi Media, 2024)
Earthquakes are a natural phenomenon that causes a very large and very detrimental disaster impact. There needs to be awareness of the importance of disaster preparedness and response to minimize the impacts of disasters. Not only for adults, children also need to be introduced to disaster preparedness from an early age. One effort that can be made to improve the preparedness of children in Elementary Schools is to provide health education and earthquake disaster preparedness simulations. The purpose of this activity is to increase elementary school students' knowledge about earthquake disaster preparedness and introduce earthquake disaster preparedness students. The method used is to provide health education through lectures, discussions, quizzes, role plays, and earthquake disaster preparedness simulations for grade VI SDN Sukajadi, Subang Regency. The results of this activity are that students have a series of practical experiences through disaster preparedness student simulations. It is hoped that schools will be able to provide an understanding through earthquake disaster preparedness education, and conduct simulations together with the Badan Penanggulangan Bencana Daerah Kabupaten Subang.